Analisis Kelayakan Pengembangan Sistem Informasi Perpustakaan SMA/SMK Kota Jambi Berbasis Web: Studi Kasus: SMKN 6 Kota Jambi - Putri Hazmawati; Edi Saputra; Muhammad Razi A; Niko Akbar; Muhammad Adfa Aditiya; Ari Prayitno (Lembaga Pengembangan Kinerja Dosen, 2025)
To support secondary education, proper facilities, including a school library, are essential. The literature in the library must be well-managed to ensure user satisfaction and comfort. However, many school libraries still rely on traditional management methods, as seen in SMKN 6 Kota Jambi's Library. To ensure the successful development of a web-based library information system, a feasibility analysis is required. This analysis helps determine if the project should proceed. This study aims to evaluate the feasibility of the system from technical, economic, and organizational perspectives. Using a descriptive approach, the research collected qualitative data through observations, interviews, and document studies, with technique triangulation to ensure validity. The findings show that the library has adequate hardware, software, and network support for the system's development, with a technical feasibility score of 75.59. The economic analysis shows an ROI of 2.3, resulting in a score of 100, and the organizational feasibility score is 93.33. The overall feasibility average is 89.64, indicating that the project is feasible.